2013
DOI: 10.1186/1475-2875-12-307
|View full text |Cite
|
Sign up to set email alerts
|

The economic costs of malaria in children in three sub-Saharan countries: Ghana, Tanzania and Kenya

Abstract: BackgroundMalaria causes significant mortality and morbidity in sub-Saharan Africa (SSA), especially among children less than five years of age (U5 children). Although the economic burden of malaria in this region has been assessed previously, the extent and variation of this burden remains unclear. This study aimed to estimate the economic costs of malaria in U5 children in three countries (Ghana, Tanzania and Kenya).MethodsHealth system and household costs previously estimated were integrated with costs asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 44 publications
9
87
2
Order By: Relevance
“…Direct prehospital costs (pre-hospitalization) differed according to the type of recourse (self-medication, health center, and traditional therapy); they were higher for households who resorted to traditional therapists and for those who consulted on-the-spot health centers before going to the hospital, compared to households who opted for self-medication. Our results confirm the observations of Sicuri et al in Ghana, Tanzania, and Kenya [27], and those of Couitchéré et al in Ivory Coast [28]. In terms of direct hospital costs, our study showed that medication and hospital stays constitute the highest proportion of costs.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Direct prehospital costs (pre-hospitalization) differed according to the type of recourse (self-medication, health center, and traditional therapy); they were higher for households who resorted to traditional therapists and for those who consulted on-the-spot health centers before going to the hospital, compared to households who opted for self-medication. Our results confirm the observations of Sicuri et al in Ghana, Tanzania, and Kenya [27], and those of Couitchéré et al in Ivory Coast [28]. In terms of direct hospital costs, our study showed that medication and hospital stays constitute the highest proportion of costs.…”
Section: Discussionsupporting
confidence: 82%
“…Health expenditures not only depend on the socioeconomic status, but also on the child's clinical picture and the care delay (time before taking the child to the hospital). Costs associated with the neurological form remained clearly higher compared to other clinical forms (anemia and respiratory distress); our results thus confirm the studies of Sicuri et al performed in Tanzania [27], and of Mulumba et al performed in the DRC [29]. The prescriber, the child's status upon leaving the hospital, and the child's age did not equally contribute to the costs in the three categories of hospitals.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The average per capita monthly income of respondents (N42,156.79) was lower than the international per capita income of employee [17]. This is an indication that the population still live below the poverty line.…”
Section: Discussionmentioning
confidence: 85%
“…[2] Over-diagnosis of severe malaria not only induces unnecessary economical burden for the patients and healthcare providers, but also leads to the failure in treating other life-threatening diseases. Sicuri et al [31] indicated that on average the cost for the treatment of severe cases of malaria, which requires hospitalization, is at least an order of magnitude higher than the treatment cost of uncomplicated malaria. Furthermore, 70% of the treatment costs were assumed by the household.…”
Section: Discussionmentioning
confidence: 99%